Derbyshire notes - Thorn, Frank; Thorn, Caroline; Morgan, Philip (The University of Hull)
The County Notes provide a discussion on all matters of interest or obscurity in the text, in the light of the latest Domesday scholarship. Such matters vary from county to county but recurrent topics include: the identification of place-names, personal names, and individuals; the meaning of obscure Latin words or phrases, or of ambiguous formulae; uncommon data; curious statistics; relevant material from related sources; variants in other editions; the state of the manuscript, including the work of individual scribes, insertions, amendments, and scribal conventions; misreadings in Domesday facsimiles; material bearing on larger Domesday topics, such as the Domesday Inquest and the date and compilation of Domesday Book; and all other items of interest. The Notes are based on the original printed edition published by Phillimore (1978) and edited by Philip Morgan. They have been fully revised and greatly enlarged for this edition by Caroline and Frank Thorn.